Work incentives and the cost of redistribution via tax-transfer reforms under constrained labor supply - Benjamin Fischer; Robin Jessen; Viktor Steiner (Freie Universität Berlin, School of Business & Economics, 2019)
Using information on desired and actual hours of work, we formulate a discrete choice model of constrained labor supply. Using the German Socio-Economic Panel and the microsimulation model STSM, we find that hours and participation elasticities are substantially smaller than those in the conventional model. We evaluate two reforms for Germany. Both redistribute to the working poor. The first reform is financed through an increase in the effective marginal tax rate for welfare recipients, the second through an increase in taxes. The first reform is desirable with equal weights, the second if the social planner has substantial redistributive taste.
urn:nbn:de:kobv:188-refubium-24961-6
Keywords: J22; H21; D10; 330; Tax-benefit systems; Household labor supply; Labor market constraints; Involuntary unemployment; Marginal cost of public funds